A look at Boaventura de Sousa Santos’ Epistemologias do Sul (Revista Brasileira Multidisciplinar, 2015)
This work is a review to discuss Boaventura de Sousa Santos’ proposal in Epistemologias do Sul (South Epistemologies), in which the author discusses the abyssal thinking of modern Western epistemology and their fragments and gaps, pointing at a ranking pattern hanging over the epistemologies, in which, epistemologies as well as cultures were also deleted in the process of colonization. It emphasizes the need for dialogue and a rescue of other forms of knowledge. This way, the post-abyssal knowledge seeks to make this bridge and understand the ecology of modern knowledge. Based on a critical analysis of his work and of his notes one can understand the core aspects that Boaventura de Sousa Santos discusses about culture, intersubjectivities and social relationships in the epistemological process and, through his study, we can understand their relationships and developments.
Keywords: South Epistemologies; Abyssal thinking; Post abyssal thinking.